Use of allopathic and complementary medicine for preventing SARS-CoV-2 infection in Mexican adults: A national survey - Alan Joel Ruiz-Padilla; Angel Josabad Alonso-Castro; Mónica Preciado-Puga; Ariadna Irais González-Núñez; José Lorenzo González-Chávez; Yeniley Ruiz-Noa; Miriam Ortiz-Cortes; Lorena Michele Brennan-Bourdon; Martha Alicia Deveze-Álvarez (Elsevier, 2021)
Background: The aim of this study was to assess the frequency of allopathic and complementary medicine use for preventing the infection with SARS-CoV-2 in Mexico. A descriptive and cross-sectional study was conducted using an online questionnaire among general adult population (n = 16,724) of the 32 Mexican states from March to November 2020. Methods: The factors associated with the use, self-medication practice, and adverse reactions due the consumption of allopathic and complementary medicine to prevent infection with SARS-CoV-2 virus were assessed using a structured questionnaire. The suspected adverse reactions associated with the use of drugs or complementary medicine were reported. Results: The prevalence (42.9%) of allopathic and/or complementary medicine use for preventing SARS-CoV-2 infection was mainly associated with unemployment [OR:2.026 (1.722-2.283)]. Acetaminophen (n = 2272) and vitamin C (n = 3252) were the main allopathic and complementary medicine products used to prevent SARS-CoV-2 infection, respectively. The prevalence of self-medication and adverse reactions was 35.3% and 4.8%, respectively. Self-medication [OR:1.930 (1.633-2.282)] and adverse reactions [OR:2.603 (2.015-3.363)] were mainly associated with individuals of low socioeconomic status. Hydroxychloroquine (21.2%) and chloroquine (15.2%) showed the highest prevalence of adverse reactions, which were mainly related to gastrointestinal disorders. Conclusion: The use of medications and complementary medicine to prevent SARS-CoV-2 infection is prevalent (almost one-half of the respondents) among Mexican population, and it is mainly associated with unemployment. Self-medication and the adverse reactions derived from self-medication are also prevalent and seem to be influenced by low socioeconomic status.